Enhanced Moisture Resistance of Salt Core through 2D Kaolinite Colloidal Solution Coating - 류소연; 류아롬; 전민석; 김동균; 홍기원; 남산; Choi, Ji Won (한국센서학회, 2023)
This study aimed to improve the moisture resistance of salt cores by investigating the suitability of a two-dimensional kaolinite colloidal solution and a commercially available SiO2 ink solution as coating agents. X-ray diffraction analysis (XRD) results showed that the intercalation of urea into kaolinite did not significantly change its layer structure. Scanning electron microscopy (SEM) images revealed that the dip-coating only affected the surface of the salt core, and the texture of the surface is differ depending on the coating solution. The humidity absorption test results showed that both coatings reduced the hygroscopicity of the salt core by more than 50%. However, in the water-solubility test, the kaolinite dissolved with the salt core, whereas the SiO2-coated salt core left a residue. These results strongly suggest that with the coating of the exfoliated kaolinite solution, salt core will remain stable in humid environments.